THE STIMULATING DIRECTIONS OF HIGHER EDUCATION INTERNATIONALIZATION IN THE PROCESS OF INTEGRATION INTO THE EUROPEAN HIGHER EDUCATION AND RESEARCH AREA - Anna Verbytska (Izdevnieciba "Baltija Publishing", 2019)
The article defines the main rationales for higher education internationalization from the perspective of the Quadruple Helix model: education- government-business-society. The paper highlights that the government sector has all four rationales for the internationalization whereas universities (mainly academic and economic ones); on the institutional level, the most preferred rationales are academic ones: international profile and status, international academic standards and research and knowledge production. The article presents the most positive impacts for higher education internationalization at the institutional level according to the results of "The EAIE Barometer: Internationalization in Europe" survey. The instruments of EU policy are the stimulating drivers for higher education internationalization in almost three-quarters of the respondents. The Erasmus+ programme was defined as the most positive impact on internationalization at respondents` HEI by the majority of respondents. At the national level, national agencies and financial support for internationalization were the most positively viewed regulations, policies and structures, while immigration and admissions regulations were defined as actual directions only in Ukraine. The article presents the priority stimulating directions of higher education internationalization in the process of integration into the European Higher Education Area: branding and competition; strategic international alliances; international dimension of the educational process; improving of the effectiveness of international project activities; implementation of academic mobility programs; attracting of foreign citizens for training. Creating an international atmosphere at the university. Currently international dimension of higher education is being increasingly promoted on the national and institutional levels in many countries. The national level has a significant influence on the international dimension of higher education through policy, funding, programs and regulatory frameworks.